Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Beef Withdrawal Time Chart - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS)
AN175 includes 19 unnumbered pages from the Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. It is a table listing product names and summarizing information on withdrawal times according to the species and the route of administration. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006.